Correlation between ICT Literacy and Pedagogic Competence of Elementary School Teachers - Sari, Pratiwi Kartika; Yuliana, Rika (Universitas Pendidikan Ganesha, 2022)
Many teachers still lack in mastering technology, information, and communication in the learning process. This study aims to reveals and analyze the correlation between ICT Literacy and the Pedagogic Competence of Elementary School Teachers. The type of this research was quantitative correlational research. The population in this study was private elementary school teachers in Bojongsari District. The research sample was 110 elementary school teachers who were taken using the cluster random sampling technique. The data collection method used was distributing questionnaires to respondents. The data analysis technique used SPSS to carry out research instrument trials, analysis prerequisite tests, and hypothesis testing using correlation coefficients and coefficients of determination to determine whether there was a correlation between ICT Literacy and Pedagogic Competence and assess how strong the effect of ICT Literacy on the Pedagogic Competence variable was. This study indicates a significant and positive correlation between ICT Literacy and Pedagogic Competence of elementary school teachers with the Pearson correlation coefficient value of 0.553. The correlation between ICT Literacy and Pedagogical Competence is in the moderate correlation category. The pedagogic competence variable is affected by ICT Literacy by 30.6%, while the remaining 69.4% is affected by other factors not discussed. It can be stated that ICT Literacy with pedagogic competence has a significant and positive correlation, and ICT can affect pedagogic competence.